Introducing Digital Otoscopes in Pediatric Primary Care Curriculum - Chelsea Wong; Daniel Nicklas; Janice Hanson; David Eckhardt (Association of American Medical Colleges, 2015)
Abstract Digital macroview otoscopy allows learners to practice visualization of the tympanic membrane and middle ear, allows faculty to ascertain that the learner has obtained an adequate view of the tympanic membrane and middle ear, and allows both learners and faculty together to describe and interpret the findings. A digital macroview otoscope shows real-time images of the middle ear during examination. This instructor's guide and the related resources equip faculty to introduce the digital otoscope to faculty and learners, which will make possible the study and evaluation of teaching with this promising technology. Learners may use this form for self-reflection, highlighting areas of the otoscopic exam that they believe need further assistance. This otoscopy tool offers a different method of teaching the ear exam that has not yet been used in medical education, and builds on previous work that shows that completion of online curricula with pictures and videos increases proficiency in identification of middle ear pathology. This project will contribute to master educator development and support efforts to improve the quality of care in the pediatric outpatient setting. The module is intended to be the first part of a series of publications highlighting the successful introduction and meaningful use of digital otoscopy in medical education. Once the curriculum has been fully developed, implemented, and evaluated, we will expand to other learners such as family medicine residents, medical students, and physician assistant students who rotate through the outpatient pediatric clinic.